RESEARCH OF INFLUENCE OF ALLOYING BY BORON ON PROPERTIES THE IRON-CARBON ALLOYS - K. V. Kobyakov; N. F. Nevar (Литьë и металлургия)
It is shown that for improvement of physical-mechanical properties of the cast products which have hard usage, the boron carbide, which can be used at carrying out process of thermo-chemical treatment of cast products of iron-carbon alloy, is of great interest.